2014
DOI: 10.2217/whe.14.48
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Features and Prognosis of Lobular Carcinoma in Egyptian Breast Cancer Patients

Abstract: ILC has distinct biologic and prognostic features that may warrant different therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
4
10
0
Order By: Relevance
“…In a sample of 75 lobular tumors from the I-SPY trial, Lips et al (2012) determined PAM50 subtypes and reported an RFD of 44% for Luminal A subtype among lobular compared to ductal tumors, similar to our findings [50]. Other studies using IHC have reported RFDs for Luminal A subtype among lobular compared to ductal tumors ranging from 6 to 39%, reflecting tremendous molecular variability in the tumors studied [14, 16, 19, 22, 37, 4749, 51, 52]. Proportions of Luminal A ductal tumors were also different between IHC subtype and RNA subtype data, suggesting RNA subtyping may be important for understanding associations between intrinsic subtype and histology.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In a sample of 75 lobular tumors from the I-SPY trial, Lips et al (2012) determined PAM50 subtypes and reported an RFD of 44% for Luminal A subtype among lobular compared to ductal tumors, similar to our findings [50]. Other studies using IHC have reported RFDs for Luminal A subtype among lobular compared to ductal tumors ranging from 6 to 39%, reflecting tremendous molecular variability in the tumors studied [14, 16, 19, 22, 37, 4749, 51, 52]. Proportions of Luminal A ductal tumors were also different between IHC subtype and RNA subtype data, suggesting RNA subtyping may be important for understanding associations between intrinsic subtype and histology.…”
Section: Discussionsupporting
confidence: 83%
“…In both studies, lobular tumors were significantly more likely to be Luminal A, both IHC- and RNA-defined, and have lower frequencies of TP53 pathway defects than ductal tumors. As previously reported, we found lobular disease to be more common among older and white women [4, 6, 10, 11, 45] more likely to be low-intermediate tumor grade, larger tumor size, and diagnosed at later stage of disease [1, 4, 6, 911, 14, 16, 17, 19, 2224, 33, 37, 4650]. However, we show that the associations between lobular subtype and patient/ tumor characteristics, with the exception of TP53 status, persisted among Luminal A subtype only, suggesting that histology contributes to these observed associations even after restricting to a single, and the dominant, molecular subtype.…”
Section: Discussionsupporting
confidence: 61%
“…In the multivariate analyses, the OS but not BCSS of lobular carcinoma NOS was better than infiltrating ductal carcinoma NOS. There are conflicting findings on the survival outcomes between lobular carcinoma and infiltrating ductal carcinoma in previous studies 18 - 20 . The median follow-up of our study was only 20 months.…”
Section: Discussionmentioning
confidence: 93%
“…Classic ILC was reported to have a better prognosis than IDC [36]. A retrospective analysis by Azimet al showed that ILC was associated with better disease-free survival[37]. Recently, another study compared the clinical outcomes between luminal IDC and luminal ILC, and found that luminal ILC had a worse outcome[38].…”
Section: Discussionmentioning
confidence: 99%